SYNTHESIS AND STRUCTURE OF HYDRAZONE DERIVATIVES OF HARMINE - Amanzhan Аsel; Zhanymkhanova Pernesh Zhaidarbekovna; Aidanuly Bauyrzhan; Shults Elvira Eduardovna; Adekenov Sergazy Mynzhasarovich; Turmukhambetov Aibek Zhursunovich (Academic Scientific Journal of Chemistry, 2020)
The present paper deals with chemical synthesis based on 8-acetylharmine. It was established that interaction of 8-acetylharmine with hydrazine hydrate produces (E)-8-(1-hydrazonoethyl)-7-methoxy-1-methyl-9Hpyrido[3,4-b]indole in a yield of 69%. It was shown, that reaction of (E)-8-(1-hydrazonoethyl)-7-methoxy-1-methyl9H-pyrido[3,4-b]indole with functionally substituted aromatic aldehydes (anisaldehyde, 2-fluorobenzaldehyde, 2,4- dimethoxybenzaldehyde) by boiling in methanol leads to the formation of the corresponding Narylidenehydrazones with 56-82% yields. The structure of the synthesized compounds was characterized on the basis of one-dimensional 1H, 13C and DEPT NMR methods, as well as data from two-dimensional COSY, HMQC, and HMBC spectra, elemental analysis and mass spectra. Correlation spectroscopic methods provided information for identification of three bond protons-protons and one bond protons-carbons correlations COSY (1 Н -1Н) and HMQC(1Н13С, 1Н15N). Homo- and heteronuclear interactions, confirming the structures of new derivatives of harmine, are determined. The use of modern physicochemical and spectroscopic research methods in the present work allowed reliable and unambiguous characterization of the structure and properties of the obtained compounds.